Team boundary spanning in a large engineering project - Kou, Chia-Yu (SAGE, 2020)
This paper reports on a qualitative study of how 12 work teams and a project-management team spanned their boundaries in a large engineering project. The study identified two types of boundary-spanning activities. Project-level managers carried out receptive activities in which they spanned boundaries vertically, adapted their management practices, and attuned themselves to the teams. Team-level managers’ activities, on the other hand, were reactive: they spanned boundaries vertically and horizontally when they needed to, and made informal connections to peer teams and project-level management. These findings underscore the important role of team boundary-spanning activities in the shape of subsequent inter-team interactions.
Keywords: teamwork; boundary spanning; multiteam project; distributed teams